Memperkuat Koneksi Akademik dan Pengalaman Lintas Budaya melalui Program “Bridging Asian Minds: Vietnam Experience”: Strengthening Academic Connections and Cross-Cultural Experiences through the “Bridging Asian Minds: Vietnam Experience” - Hendy Endarwan; Gary Putra Etwanto; Tiolina Evi (OGZ Research & Publishing, 2025)
Objective: The academic and cultural exchange between the University of Economics and Finance (UEF), Ho Chi Minh City, Vietnam, and the Perbanas Institute, Indonesia, held from August 8–9, 2025, was a huge success. The program, themed